Heterosis of okra resistance sources for okra yellow vein mosaic virus (OYVMV) in okra (Abelmoschus esculentus) - SOLANKEY, S S; SINGH, A K; SINGH, R K (The Indian Journal of Agricultural Sciences, 2016)
Fifty one hybrids of okra [Abelmoschus esculentus (L.) Moench] were generated by crossing between seventeen lines and three testers. Seventy one (20 parents + 51 hybrids) genotypes were used for screening against okra yellow vein mosaic virus (OYVMV) in open field condition and studied the heterosis for disease resistance and associated yield traits during rainy season and summer season of 2007 and 2008. The disease pressure of OYVMV was high in rainy season crop because of high humidity and rainfall along with more multiplication of whiteflies. Eight parents (VRO 5, VRO 6, AC 108, Arka Abhay, EC 305612, IIVR 435, IIVR 401 and SA 2) and 30 and 33 F1 crosses were found highly resistant for OYVMV disease during both rainy and summer season. Summer season crop was more producible for number of fruits and fruit yield/plant than rainy season crop due to low disease incidence. Those crosses which involved the parents IIVR 198, SA 2, Arka Abhay, AC 108, and VRO 5, gave better heterosis performance for disease resistance and associated yield traits.